Effectiveness of the Flipped-Blended Learning Model in Computer and Network Engineering Education - Noer Ekafitri Sam (Information Technology Education Journal, 2025)
Research on Flipped-Blended Learning in vocational education has grown in recent years; however, empirical evidence focusing specifically on Computer and Network Engineering (TKJ) competencies in Indonesian vocational high schools remains limited. Previous studies primarily examined general blended learning implementation without addressing learning challenges unique to TKJ, such as limited practical time, low preparedness for autonomous learning, and the need for stronger conceptual mastery prior to hands-on practice. This study aims to evaluate the effectiveness of a Flipped-Blended Learning model implemented through a LMS at SMKN YPPP Wonomulyo and SMKN 1 Tinambung. Using a quasi-experimental one-group pretest–posttest design, data were collected from 30 students through cognitive tests, observation sheets, questionnaires, and LMS usage logs. Results indicate a medium-to-high increase in cognitive outcomes based on normalized gain. Student activity categorized as very active, particularly in accessing digital resources, completing online assignments, and participating in LMS-based discussions. These findings demonstrate that the Flipped-Blended Learning model effectively enhances conceptual understanding, active engagement, and independent learning in TKJ subjects. This study contributes by providing student-centered evidence on the integration of LMS-based flipped learning in vocational engineering contexts. Practical implications suggest that teachers need to systematically design pre-class digital materials and optimize face-to-face sessions for collaborative problem-solving and practice.